Strategies for promoting bancassurance products in West Java: a study of Bank XXX's internal and external factors - Alan Setia Suganda; Atik Aprianingsih (Goodwood Publishing, 2025)
Purpose: The Theory of Planned Behavior (TPB), a psychological study that aims to comprehend human behavioral tendencies, was applied. This study aims to examine the methods employed by Bank XXX West Java to market assurance products. Research methodology: To gather quantitative data, questionnaires and descriptive analyses were used to investigate Bank XXX Indonesia's internal strategies, including Segmentation, Targeting, and Positioning (STP), as well as the expanded 7Ps. PESTLE, SWOT, TOWS matrix, and customer analyses were also used for external analysis. Results: The recommendations of this study emphasize the need for continuous market analysis to improve strategies and explore potential areas for future research in the field. To deepen the understanding of consumer behavior in the banking industry, future studies could focus on the marketing mix and delve into consumer behavior and decision-making processes. Conclusion: Strategic marketing initiatives aligned with TPB constructs—attitude toward behavior, subjective norms, perceived behavioral control, perceived risk, and trustworthiness—significantly influence purchase intention and loyalty, highlighting the value of integrating psychological behavior models with marketing frameworks to enhance customer engagement and retention. Limitations: This research aims to provide theoretical insights into practical applications, valuable industry insights, and opportunities for further exploration of customer behavior in the banking industry. Implementation: A direct relationship between purchase intention and loyalty was discovered. Customers who were satisfied with Bank XXX West Java had a higher attitude towards behavior, subjective norms, perceived behavioral control, perceived risk, and trustworthiness.